Biologiya ta‘limida talabalar ekologik madaniyatini shakllantirishda innovatsion metodlar (SCIENCE and SOCIETY, 2023)
The article describes the organization of innovative processes, the content and essence of the concepts of "Innovative educational technologies" and "educational innovations", holding environmental days.